Educação financeira nas escolas: uma exigência contemporânea. E agora, como fazer? - Souza, Amélia Jandrea de (2021)
The challenge when developing resources for teaching is to seek materials, methods and models that are innovative and go beyond the traditional teaching model, based only on the transfer of informatio n from the teacher to the student. In order to build a more interactive classroom, with meaningful and active learning, teachers and students are led to demand pedagogical resources for these new models, especially those that relate theory, practice and the student's reality. The National Common Curricular Base BNCC determines the curricular bases for all stages of basic education, including High School, and guides that the approach of Transversal Contemporary Themes TCTs, among them Financial Education , is mandatory and can be done in an interdisciplinary, transdisciplinary or project based way. However, as it is a new requirement for the curriculum, there is still a shortage in the supply of resources for technical and technological education built wit h the purpose of working on this theme specifically in the classroom. Here is the problem faced in this research: in what way is it possible to work on Financial Education as a contemporary and transversal theme, uniting theory and practice and encompassin g the competences and abilities to be developed by students of Technical Courses of Secondary Level in an Integrated way? The research was developed with the objective of elaborating a didactic resource that was aimed at the teaching learning of Financial Education, mainly involving practical activities, so that teachers could use this resource in the classroom as a way of complementing theoretical classes, from the perspective of critical financial education, in order to help students build skills and comp etences for their decision making in real life, taking into account social scenarios. This research had a qualitative character, following procedures of bibliographic, documentary and action research. The bibliographic research guided, contextualized and f ounded the central object of study, Financial Education. The documentary research investigated the documents that guide the Technical High School in an integrated way, mainly regarding the insertion of Financial Education in the curriculum. Action research guided our entire methodological procedure to work in the classroom with students, in a transversal and interdisciplinary way, through theoretical classes and practical activities with students from the Technical Course in Management Integrated to High Sc hool of the 1st, 2nd and 3rd year of the Federal Institute of Amazonas IFAM/Campus Maués. The instruments used were semi open questionnaires and interviews. The methodological procedure was developed from the diagnosis, intervention and evaluation of res ults. For the intervention, 8 face to face meetings were held, 4 to work on the expository classes of each module, in addition to the initial meeting to apply a questionnaire and in the last 3 meetings we had the financial games fair. Finally, the results how that the resource developed during the research, the financial game "Balancing the Budget" is a good strategy for an effective learning of Financial Education, which should be considered by teachers as an alternative to complement the theoretical clas ses and make the contents more attractive, interactive and, above all, understandable and feasible, as this educational product awakens in the student the motivation and interest in financial education content that is difficult to understand and provides a n opportunity for teaching and learning Financial Education in a broad, practical and contextualized way.